Who's behind an HCAHPS score? - Wild, Dorothea M G; Kwon, Nancy; Dutta, Suparna; Tessier-Sherman, Baylah; Woddor, Navitha; Sipsma, Heather L; Rizzo, Tara; Bradley, Elizabeth H (Joint Commission journal on quality and patient safety / Joint Commission Resources, 2011)
The Hospital Consumer Assessment of Health Care Providers and Systems (HCAHPS) survey asks patients how frequently their physicians treated them with courtesy and respect, listened carefully, and explained things in a way they could understand. Such summary reports may obscure differences among the types of physicians involved. A study was conducted to examine the association between ratings for different physician types and the overall HCAHPS rating of physicians.
Keywords: Adult; Aged; Attitude of Health Personnel; Communication; Female; Hospitalists; Humans; Male; Middle Aged; Patient Care Team; Physician-Patient Relations; Quality of Health Care; Socioeconomic Factors; Specialization